Effect of different dental burs for experimental induction of pulpitis in mice. (November 2017) - Shi, Xilin; Li, Zhengmao; He, Ying; Jiang, Qianzhou; Yang, Xuechao
Highlights: A stable pulpitis model in mice can be produced by a ¼ round bur or polishing bur. The progress of pulpitis induced by a polishing bur is relatively slow. The different progress was accountable mainly to different levels of irritation. The slow progress of pulpal inflammation could be useful in future molecular research. Abstract: Objective: To evaluate the effect of using different dental burs on the development of pulpal inflammation after pulpal exposure in mice. Design: Eighty-eight C57 BL/6 mice were randomly assigned to group A (n = 40), group B (n = 40) and control group (n = 8). The pulps of the maxillary first molars were occlusally exposed using ¼ round burs and polishing burs in group A and B respectively. Animals were sacrificed randomly at 0 h, 4 h, 8 h, 12 h and 24 h after pulpal exposure. Micro-CT scanning was used to determine the success rate of sample preparation. Pulpal tissue changes were evaluated by histopathologic and immunohistochemical analyses. Results: The success rates of sample preparations were 85% in group A and 90% in group B. The mean maximum diameter of pulpal exposure area was 625.6 ± 30.6 μm in group A and 402.7 ± 18.0 μm in group B ( p < 0.05). In addition, the mean of the minimum remaining dentine thickness at the marked region of interest was 133.2 ± 29.9 μm in group A and 261.4 ± 16.3 μm in group B ( p < 0.05). Histopathologic staining demonstrated more signs of inflammation in both groups, as the duration of pulpal exposure increases. However, the rate of inflammatory progress was higher in group A, even spreading to the root pulp tissue within a few hours. For group B, the progress was relatively slow. Conclusions: Pulpal exposure with different sizes of dental burs affects changes in the development of pulpal inflammation in mice.